Cocoa and Objective-C : up and running - Stevenson, Scott (O'Reilly Media, 2010)
With this book, you'll learn how to use Apple's Cocoa framework and the Objective-C language through step-by-step tutorials, hands-on exercises, clear examples, and sound advice from a Cocoa expert.--[book cover].